PENGARUH JUMLAH PENGINAPAN, JUMLAH PEDAGANG MINUMAN BERALKOHOL, DAN JUMLAH PENDUDUK TERHADAP RETRIBUSI DAERAH PADA KABUPATEN/KOTA DI PROVINSI BALI - Artha Wiguna, I Wayan Wahyu; Karmini, Ni Luh (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2022)
Regional autonomy policies have implications for local governments. The implementation of decentralization reduces the role and contribution of the central government to local governments, so that local governments need to prepare relatively large funds. The purposes of this study are to analyze the effect of the number of lodging, the number of alcoholic beverage traders, and the number of residents simultaneously and partially on regional levies in the Regency/City in Bali Province and to know the variables that have the most dominant influence on the retributions to the regencies/cities in the province of Bali. The data used is secondary that 45 observations are obtained. The analysis technique used is multiple regression analysis. The results showed that (1) the number of lodging, the number of alcoholic beverage traders, and the number of residents simultaneously had a significant effect on regional levies in the Regency/City in Bali Province, (2) the number of lodging, the number of alcoholic beverage traders, and the number of residents partially affected positive on regional levies in regencies/cities in Bali Province, and (3) the number of lodging is the variable that has the most dominant influence on regional levies in regencies/cities in Bali Province. Keywords: Regional Levies, Lodging, Alcoholic Beverage Traders, Residents